2018
DOI: 10.17221/75/2017-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell characteristics and cuticle deposition in three laying hen genotypes housed in enriched cages and on litter

Abstract: Ketta M., Tumova E. (2018): Eggshell characteristics and cuticle deposition in three laying hen genotypes housed in enriched cages and on litter. Czech J. Anim. Sci., 63, 11-16.The objective of the present study was to compare the eggshell characteristics and cuticle deposition of Lohmann Brown, Hy-Line Silver Brown, and Isa Brown layers kept in two different housing systems. The three laying hen genotypes were housed in enriched cages (100 hens, 750 cm 2 /hen, 10 hens/cage) and in littered pens (100 hens, 9 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Rutkowski et al [7] reported a significant association between the egg production date and egg weight, the proportion of shell in the egg and shell thickness, measured in weeks 5 (5.30 g; 9.70%; 0.357 mm) and 13 (5.90 g; 9.50%; 0.366 mm). Differences in the analysed egg traits, both in the present study and studies reported by other authors, may result from the structure of the shell, particularly from the crystalline layer of the shell and the content of minerals [41].…”
Section: Discussionsupporting
confidence: 44%
“…Rutkowski et al [7] reported a significant association between the egg production date and egg weight, the proportion of shell in the egg and shell thickness, measured in weeks 5 (5.30 g; 9.70%; 0.357 mm) and 13 (5.90 g; 9.50%; 0.366 mm). Differences in the analysed egg traits, both in the present study and studies reported by other authors, may result from the structure of the shell, particularly from the crystalline layer of the shell and the content of minerals [41].…”
Section: Discussionsupporting
confidence: 44%
“…A non-significant effect of the housing system was detected in our study for eggshell quality parameters. A non-significant effect of the housing system on some eggshell quality parameters, namely eggshell strength and thickness, were detected in our previous study [ 25 ]. Moreover, Kühn et al [ 44 ] concluded that the housing system had no effect on the eggshell weight and eggshell thickness of eggs from the littered floor and free-range systems.…”
Section: Discussionmentioning
confidence: 86%
“…Singh et al [ 3 ] recommended that the hen genotype should be considered when choosing the housing system. Several studies have been done in order to evaluate the effect of a two-way interaction on hen performance and eggshell quality parameters such as the housing system and genotype [ 6 , 25 ], feed Ca level and age [ 23 ], genotype and feed Ca level [ 26 ], and housing system and age [ 27 , 28 ]. Despite that, few studies gave attention to the effect of a three-way interaction of different factors on hen performance and eggshell quality parameters.…”
Section: Introductionmentioning
confidence: 99%
“…After measuring eggshell strength, the eggs were broken and the internal egg components were kept for further analysis. Eggshell thickness was measured with a QCT shell thickness micrometer (TSS) at the equatorial region after removal of shell membranes (Ketta and Tumova 2018a). Eggshell weight was determined after complete drying.…”
Section: Experimental Design Genotype and Managementmentioning
confidence: 99%